A rare manifestation of scarlet fever with a staphylococcal abscess - R. M., Kavyadeepu; Sekar, Mohnish (International Journal of Research in Dermatology, 2026)
Scarlet fever is a bacterial infection distinguished by a growing fever and a rapid rash, usually accompanied by pharyngitis, and can give rise to severe ramifications. We report a case of scarlet fever characterized by a sandpaper rash and strawberry tongue, accompanied by an atypical gluteal abscess. Streptococcus pyogenes had been isolated from a throat swab, whereas Staphylococcus aureus was recovered from a gluteal abscess at the assessment. The patient exhibited improvement with suitable treatment, devoid of adverse effects.